FREQUENCY OF H. PYLORI INFECTION IN PERFORATED PEPTIC ULCER PATIENTS - Tayyeb Ullah; Suliman Shah; Haider Ali; Muhammad Marwan; Sidra Jabeen; Khalid Habib (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Peptic ulcer disease is a common medical problem with a lifetime prevalence of 5-10% and an incidence of 1.5-3% in general population per year.Objective: To determine the occurrence of H. Pylori infection in patients with perforated peptic ulcer.Setting: Department of Surgery, Lady Reading Hospital, Peshawar, PakistanStudy design: Cross sectional Study.Duration of study: Six months from 4th August 2020 to 4th February, 2021.Materials and methods: In the current study a total of 171 patients were observed. Data like patient age, sex, history of Non-steroid anti-inflammatory drugs usage in last 10 days and history of peptic ulcer disease was noted. Patients were managed and were prepared for surgical intervention as per protocol. During surgery the biopsy from perforation site was taken and was sent for culture & sensitivity. IBM-SPSS Version.23 was used for analysis of data.Results: In the current study, a total of 171 patients were enrolled. In our study, 150(87.72%) patients were male and 21(12.28%) patients were female. 79(46.2%) patients had positive history of NSAID usage and 92(53.8%) patients had negative history of NSAID usage. 93(54.4%) patients had helicobacter pylori infection and 78(45.6%) patients didn’t had helicobacter pylori infection.Conclusion: Our study concludes that the frequency of H. pylori infection was 54.4% in perforated peptic ulcer patients.